2015
DOI: 10.1089/pho.2015.3911
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Low-Level Laser Therapy on Oral Mucositis and Quality of Life in Patients Undergoing Hematopoietic Stem Cell Transplantation Using the Oral Health Impact Profile and the Functional Assessment of Cancer Therapy-Bone Marrow Transplantation Questionnaires

Abstract: LLLT did not influence the oral and general health-related QoL of patients undergoing HSCT, although it was clinically effective in reducing the severity of chemotherapy-induced OM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 25 publications
1
10
0
2
Order By: Relevance
“…It is added that, in another study, Silva et al, (2014) [25], observed that 72.8% of patients on preventive laser therapy protocol also did not developed the condition. It is emphasized that, among the patients evaluated in the present study who presented mucositis, most were classified in grade 1, where there is no ulcer, as observed in the works by Silva et al, (2015) [26] and Bezinelli et al, (2015) [3], who evaluated patients under a preventive protocol.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…It is added that, in another study, Silva et al, (2014) [25], observed that 72.8% of patients on preventive laser therapy protocol also did not developed the condition. It is emphasized that, among the patients evaluated in the present study who presented mucositis, most were classified in grade 1, where there is no ulcer, as observed in the works by Silva et al, (2015) [26] and Bezinelli et al, (2015) [3], who evaluated patients under a preventive protocol.…”
Section: Discussionsupporting
confidence: 63%
“…The most used preventive protocol was Laser V, 2J, 20sec, although the protocols are quite variable in the literature, which is a major limitation for the establishment of an effective standard protocol for the prevention of oral mucositis. Even so, there is a certain standardization for the use of red spectrum laser for prevention [23,26,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, data gained can introduce a comparison between the two instruments, as our literature review did not reveal any study comparing data from the OHIP-14 and the FACT-Head and Neck instruments. There was however, one study found which compared OHIP-14 to another member of the FACIT family, namely the FACT-Bone Marrow Transplant [13].…”
Section: Comparison Of Quality Of Life Instrumentsmentioning
confidence: 99%
“…La TLBI actúa principalmente sobre el citocromo c-oxidasa, flavinas y las porfirinas las cuales absorben ciertas longitudes de ondas (rojas-infrarrojas),que resulta en la producción de energía para desarrollar los procesos metabólicos de las células, mejorar la microcirculación, aumentar la proliferación y movilidad de las celulas epiteliales y fibroblastos para que aceleren la síntesis de colágeno y así disminuir las especies reactivas de oxígeno. Estudios recientes sugieren que la TLBI activa factores de transcripción, citoquinas y quimioquinas, generando un mecanismo de protección en los tejidos, aumentando los niveles de citoquinas antiinflamatorios como (IL-10) (Silva et al, 2015).…”
Section: Introductionunclassified